Manipulating the magnetic anisotropy in the ferromagnetic semiconductor Gallium Manganese Arsenide - Casiraghi, Arianna (2012)
Since its first successful growth in 1996, the ferromagnetic semiconductor (Ga,Mn)- As has had a great inuence on the research field of semiconductor spintronics. Among the outstanding characteristics of this material the large spin-orbit interaction for the holes in the valence band plays a major role, since it is responsible for some of the most interesting properties of (Ga,Mn)As, like the magnetocrystalline anisotropy, the magnetoelastic coupling and the extraordinary contributions to the magnetotransport. Furthermore, the combination of large magnetic anisotropies, large spin stiffness and relatively small magnetic moments renders (Ga,Mn)As a hard ferromagnetic system with excellent micromagnetic properties, including mean-field like magnetization and macroscopic single-domain characteristics, that can be described both phenomenologically and microscopically, thanks to the relatively simple band structure. Finally, the interplay between ferromagnetism and semiconductivity, arising from the hole-mediated nature of the ferromagnetic interaction in (Ga,Mn)As, allows for the remarkable possibility of manipulating its magnetic properties by varying the state of the holes using non-magnetic parameters like electric fields, electric currents, light or strain. This circumstance could in principle be very useful to improve the process of writing information in magnetic memories, which is currently performed, not very efficiently, with magnetic fields. However, it does seem unlikely that (Ga,Mn)As will become a relevant material for technological applications since the highest Curie temperature so far obtained for (Ga,Mn)As is still well below room temperature. Nonetheless the study of (Ga,Mn)As remains a fervent research area since it allows to explore a variety of novel functionalities and spintronics concepts that could in future be implemented in other systems. For this reason (Ga,Mn)As is often referred to as a test bench material for semiconductor spintronics. This Thesis presents the results of a series of experimental investigations showing how dfferent approaches can be used to manipulate the magnetic anisotropy in (Ga,Mn)As thin films. In Chapter 4 the properties of the ferromagnetic semiconductor (Ga,Mn)(As,P) are investigated through structural, magnetometry, transport and magnetotransport measurements. By varying the amount of phosphorus incorporated it is possible to vary the sign of the in-built growth strain, to which the magnetic anisotropy in (Ga,Mn)As is extremely sensitive. It is in fact shown that samples with large enough phosphorus concentrations are characterized by a perpendicular-to-plane magnetic easy axis, which is an extremely useful property since it allows to detect the orientation of the magnetization via anomalous Hall effect and polar magneto-optical Kerr effect. Furthermore, it is demonstrated that by varying the temperature or the post-growth annealing time it is possible to obtain a reorientation of the magnetic easy axis from an in-plane direction to the perpendicular-to-plane direction in some samples, which is another interesting aspect of this material. Chapter 5 consists of a study exploring the effects of piezoelectric-induced strain on the magnetic anisotropy of a highly-doped annealed (Ga,Mn)As sample bonded to a piezoelectric actuator. It is shown that large and reversible rotations of the magnetic easy axis can be achieved in this sample by varying the voltage applied to the piezoelectric actuator, thus demonstrating that strain-mediated electric control of ferromagnetism is effective even in the limit of high doping levels and high Curie temperatures, where direct electric control of ferromagnetism via carrier manipulation is not possible. Furthermore, the results obtained from magnetotransport and SQUID magnetometry measurements are compared, extracting the dependence of the piezo-induced uniaxial magnetic anisotropy constant upon strain in both cases and discussing why the magnetotransoport measurements are believed to be more accurate than SQUID magnetometry measurements in evaluating the inverse magnetostriction effects in (Ga,Mn)As-piezoelectric actuator hybrid systems. Finally, Chapter 6 contains the results of an investigation attempting to use ultrashort strain pulses to switch the magnetization direction in a (Ga,Mn)(As,P) sample on fast time scales. These pulses are generated by femtosecond optical excitation of a metal transducer film deposited on the back of the substrate and travel ballistically through it until they reach the sample under investigation. Despite demonstrating that this method can indeed be used to induce a fast irreversible switching of the magnetization orientation in the (Ga,Mn)(As,P) sample, time-resolved magnetotransport measurements show that the switching is not triggered by the strain pulse, but rather by the transverse heat pulse, the latter being generated with the strain pulse during the optical excitation of the metal film. It is shown that the switching occurs through domain-related processes and the possible mechanisms behind its cause are speculated.